Masters vs Job: Factors which Help Students to Decide between the Two - Ramandeep Singh; Mansi Chaudhary (International Journal of Engineering and Management Research, 2020)
The main idea of the study is to find out the factors that affect the key decision which results in choosing of one option between pursuing a master’s degree after college or going for placement after graduation. Researcher has collected data from 120 college going students and graduates. The data was accumulated using Google forms, it was analysed using Google’s analytical instruments. It was found out that students do not follow any trend to pursue their next goal but they decide upon factors which are directly or indirectly related to their personal lives and circumstances. Although most common answer recorded during the survey was that how some students do not want a break amidst their studies and on other hand some of them want to learn and gain practical experience.